Analisis Tingkat Pendapatan Petani Tanaman Hias di Distrik Heram Kota Jayapura - Tanudy, Ayub (Rifa'Institute, 2022)
Ornamental plant commodities are commodities that are loved by many people because they have high artistic value. Realizing this, the farmers are trying to take advantage of the land they rent to develop the ornamental plant business. Ornamental plants that are sold apart from coming from the results of their own culture by farmers are also imported from outside the Papua region, namely from the island of Java. Until 2021, there are seven farmers who run ornamental plant businesses in the Heram District of Jayapura City. The number of consumers also varies, some from the city and district of Jayapura itself, some from other cities in the provinces of Papua and West Papua. This encourages farmers to produce more vigorously in order to meet these demand standards. In addition, the important thing that needs to be considered by ornamental plant farmers is the fertility and quality of ornamental plants. This study aims to analyze the income level of ornamental plant farmers. In connection with the objectives to be achieved, the analytical method used by the author in this thesis is the quantitative analysis method to calculate the income level of farmers, with the formula: = TR – TC. So this study shows that the total income of farmers obtained in 2021 ranges from Rp. 7,457,500 – Rp. 16,565,000. Where the highest level of income is respondent 2, namely Rp. 16,565,000 and the lowest is respondent 6, which is Rp. 7,457,500.